'Backward' industrialisation in resource-rich countries: The car industry in Uzbekistan. (July 2023) - Galdini, Franco
This article analyses the 'backward' form of import-substitution industrialisation (ISI) in countries integrated into the global economy as exporters of primary commodities, using the example of the car industry in Uzbekistan. This form of incorporation defines the way in which all manufacturing capitals, regardless of 'nationality', accumulate at the average rate of profit via raw material rents, as mediated by specific state policies. This has been the case of Uzbekistan's state-owned car manufacturer UzAvtoSanoat, in joint-venture with Korean Daewoo Motor Company and American General Motors in the 1992–2016 period. Orthodox ('neoliberal') economists view the Uzbek car industry as inefficient due to state intervention. Heterodox ('developmental state') scholars hail it as an example of export-oriented industrial upgrading. Neither explain, however, why leading MNCs would invest in such an inefficient market (as per the former), given its low scale of production that is mostly purchased domestically (pace the latter). Instead, I contend that all manufacturing capitals in the country could stay profitable only via rent subsidisation, the main reason for leading MNCs to invest in it. As such, 'backward' manufacturing ISI in Uzbekistan epitomises a specific national form taken by the global process of capital accumulation in resource-rich countries of the Global South.